Pengaruh Penerapan E-System Perpajakan, Kesadaran Wajib Pajak, dan Sanksi Pajak Terhadap Kepatuhan Perpajakan Wajib Pajak Orang Pribadi - Delvechio, Vieri; Pahala, Indra; Utaminingtyas, Tri Hesti (LPPM Universitas Negeri Jakarta, 2023)
The Taxpayer compliance is important to avoid causing tax evasion, smuggling, and other tax problems. The aim of this research is to analyze the influence of the tax e-system, taxpayer awareness, and tax penalties on tax compliance. The samples using simple random sampling technique was 120. In this study, data is gathered using a Google Form survey administered to individual taxpayers in KPP Pratama Jakarta Kebayoran Lama. With SPSS 25, multivariate analysis was used to analyze the data and the hypothesis. The results show that taxpayer awareness and tax penalties have a significant effect on taxpayer compliance. Whereas the tax e-system has no significant effect.